MHD Flow of Nano-Fluid with Non-Uniform Heat Source or Sink in the Presence of Chemical Reaction and Activation Energy - Akindele, Akintayo; Wale, Ogunsola Amos; Obalalu, Adebowale Martins; Peter, Adegbite; Adebayo, Ajala Olusegun; Alao, Saheed (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2021)
The study of squeezing flow  cannot be over emphasized due to its numerous applications in manufacturing industries, food processing, lubricating system, power transmission and medical equipment are few of such processes. This calls for more studies in the area of squeezing flow. MHD flow of nano-fluid with non-uniform heat source or sink in the presence of chemical reaction and activation energy were considered. The governing partial differential equations were transformed to ordinary differential equations in terms of suitable similarity variables together with the initial and boundary conditions. The resulting equations were then solved using Newton’s finite difference technique with the aid of MAPLE 18.0 software. The effect of radiation, magnetic parameter, temperature dependent heat source parameter, surface dependent heat source parameter and other associated physical parameters on the flow system were reported.